a-37=93

Simple and best practice solution for a-37=93 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a-37=93 equation:



a-37=93
We move all terms to the left:
a-37-(93)=0
We add all the numbers together, and all the variables
a-130=0
We move all terms containing a to the left, all other terms to the right
a=130

See similar equations:

| 3y+−4.9=2.6 | | h/0.5×0.5=7/0.5 | | w=V25 | | 3(a-29)+29=224 | | 4(x+4^2+23=27 | | x(x+28)=20*52 | | 135/32=x/160 | | 2z^2+z=0 | | 2z+15=49 | | (4x+2)=(7x-6) | | 2n^{2}-8n-24=0 | | (2n=4) | | 5^0.1x=10/3 | | 4n−6=10n+7 | | 5x-4=6x=2 | | (3x+6)/2=5/4 | | 2x=√-5x+24-3 | | 24y+3y=21 | | -4(x)=2x2-1 | | y-0.9y=4400 | | k/5+4=2 | | 5x10=10x | | 7+m/2=16 | | (4+0.03y)*(2-y)=8 | | Y=2x;(1/4) | | 14+a/6=4 | | -5-10m=-175 | | n/7-6=-4 | | b/7-9=-6 | | v/2-12=-18 | | n/5=30. | | 6+v/16=9 |

Equations solver categories